Understanding emotionally involved publics: The effects of crisis type and felt involvement on publics' emotional responses to different consumer product crises. (3rd October 2016) - Kim, Jeesun; Jin, Yan
Abstract : Purpose: The purpose of this paper is to examine the interplay of crisis type and felt involvement as well as product category on publics' anger toward the company and empathy for the victims. Design/methodology/approach: This study uses an experiment based on a 2 (crisis type: accident vs transgression) × 2 (publics' felt crisis involvement: high vs low) × 2 (product category in crisis: food-related vs technology-related) mixed design. Findings: Differential main effects on emotions were detected in different consumer product crises. One of the most interesting findings in this study was the main effects of high felt involvement over low felt involvement in strong feelings of anger toward a company and empathy for the victims in both food- and technology-related crisis situations. There was an interaction effect between crisis type and product category on feelings of anger toward a company. Participants in the food-related crisis condition reported more anger when exposed to a transgression crisis than an accident crisis. Research limitations/implications: Future research needs to study other important crisis emotions and to measure them with multiple items instead of a single item. It would be useful to find out what combinations among crisis variables would produce interaction effects to better understand how different publics' emotions are inducted and processed in different crisis situations. Practical implications: The role of felt involvement on public emotions may not be product category specific, but rather be affectively influential across different product categories. From the standpoint of crisis management practice, the main contribution of the present study is to provide empirical evidence that crisis communication managers could use the level of publics' felt crisis involvement to better predict publics' emotions that are likely to be felt and displayed in crisis situations. Originality/value: This study investigates the crisis-generated discrete emotions as a function of crisis type and felt involvement. Felt involvement should be considered as an important construct due to its potential consequences on publics' emotions and their behaviors beyond perceptions of crisis responsibility. Crisis response messages should be strategically developed with a consideration of the interplay of crisis type, publics' felt involvement, and product categories.